Iridoid glycosides isolated from Nardostachys chinensis batal with NO production inhibitory activity. Issue 7 (3rd April 2022) - Xue, Gui-Min; Zhao, Chen-Guang; Xue, Jin-Feng; Zhao, Zhen-Zhu; Si, Ying-Ying; Du, Kun; Sun, Yan-Jun; Feng, Wei-Sheng
Abstract: Investigation into the chemical diversity of Nardostachys chinensis Batal led to the discovery of three new (1 –3 ) and one known (4 ) iridoid glycosides. Their structures were established through spectroscopic methods including 1 D and 2 D NMR experiments and HRESIMS analysis. Inhibitory effects of 1 –4 on nitric oxide production were investigated in lipopolysaccaride (LPS)-mediated RAW 264.7 cells, and they displayed IC50 values in the range 7.8–15.2  μ M. Graphical Abstract: